Ball‐Milling Induced Debonding of Surface Atoms from Metal Bulk for Construing High‐Performance Dual‐Site Single‐Atom Catalysts. Issue 43 (13th September 2021) - Wang, Huilin; Wang, Xiao; Pan, Jing; Zhang, Lingling; Zhao, Meng; Xu, Jing; Liu, Bo; Shi, Weidong; Song, Shuyan; Zhang, Hongjie
Abstract: One of the most pressing challenges in single‐atom catalysis is the manipulation of the coordination environment of central metals to maximize the catalyst performance. Herein, we fabricated a high‐performance catalyst (Co‐SNC) by introducing S into the neighboring position of the Co‐N4 coordination. The developed ball‐milling method enabled large‐scale synthesis, that over 4.7 g of Co‐SNC can be produced in one pot. In benzylamine coupling reaction, Co‐SNC exhibited the highest conversion of 97.5 % with 99 % selectivity toward N ‐benzylidenebenzylamine in 10 h among various Co catalysts. Density functional theory calculations revealed the crucial role of S atoms, which serve as the active sites for O2 activation, leaving the Co atoms free to adsorb benzylamine. Consequently, the adsorption energies of O2 and benzylamine were significantly increased. Our strategy suggests a feasible approach to enhance catalytic performance by delicately integrating dual active sites into a single catalyst unit. Abstract : S, N co‐doped carbon immobilized Co single atoms exhibit superior performance in amine self‐coupling reaction, which can be attributed to the superiorities of such dual‐site catalysts in boosting O2 activation and amine adsorption, simultaneously.